Analisis Evaluasi Pembelajaran Sejarah Berbasis Aplikasi Edmodo Di SMA Negeri 1 Pontianak - Marsudi, Muhammad Ramadhan; Firmansyah, Andang; Firmansyah, Harris (Peneliti.net, 2024)
The aim of this research is to obtain information and clarity regarding the evaluation analysis of history learning based on the Edmodo application at SMA Negeri 1 Pontianak. This research uses qualitative research methods in descriptive form. The data sources for this research are history subject teachers, curriculum leaders, students and data in the form of interview results. The results of the research can be concluded that. (1) in planning history learning using the Edmodo application, the teacher has planned learning evaluation activities to be achieved on competency achievement indicators, namely cognitive, affective and psychomotor aspects. (2) in implementing history learning based on the Edmodo application, the teacher gives questions and assignments with a time limit to improve cognitive and affective aspects, while in the psychomotor aspect, the teacher gives students assignments for making videos. (3) the obstacles encountered while using the Edmodo application as a media for evaluating history learning are students' lack of attention to the teacher's instructions in the process of working on questions and some students often experience network problems when doing assignments using this application.